Overweight, Obesity, and Lung Function in Children and Adults-A Meta-analysis - Forno, Erick; Han, Yueh-Ying; Mullen, James; Celedón, Juan C (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2018)
There is conflicting evidence on the effect of obesity on lung function in adults and children with and without asthma. We aimed to evaluate the relation between overweight or obesity and lung function, and whether such relationship varies by age, sex, or asthma status. We searched PubMed, Scopus, CINAHL, Cochrane, and EMBASE for all studies (in English) reporting on obesity status (by body mass index) and lung function, from 2005 to 2017. Main outcomes were forced expiratory volume in 1 second (FEV ), forced vital capacity (FVC), FEV /FVC, forced expiratory flow between 25th and 75th percentile of the forced vital capacity (FEF ), total lung capacity (TLC), residual volume (RV), and functional residual capacity (FRC). Random-effects models were used to calculate the pooled risk estimates; each study was weighed by the inverse effect size variance. For each outcome, we compared overweight or obese ("obese") subjects with those of normal weight. All measures of lung function were decreased among obese subjects. Obese adults showed a pattern (lower FEV , FVC, TLC, and RV) different from obese children (more pronounced FEV /FVC deficit with unchanged FEV or FVC). There were also seemingly different patterns by asthma status, in that subjects without asthma had more marked decreases in FEV , TLC, RV, and FRC than subjects with asthma. Subjects who were obese (as compared with overweight) had even further decreased FEV , FVC, TLC, RV, and FRC. Obesity is detrimental to lung function, but specific patterns differ between children and adults. Physicians should be aware of adverse effects of obesity on lung function, and weight control should be considered in the management of airway disease among the obese.